Avaliação da relação entre parâmetros clínicos patológicos de pacientes portadoras de câncer de mama frente à concentração de quimiocinas - Silva, Paulo Henrique Rosa da (2021)
Breast cancer is the most frequently diagnosed cancer in women and ranks second among the causes of death from cancer. It is a heterogeneous disease, and its pathogenesis remains unclear in most cases. This work evaluated the relationship of four specific types of chemokines with clinical pathological characteristics of patients with breast cancer at the Hospital de Clínica de Uberlândia. The quantification of chemokines in the patients' serum was performed using the LegendPlex technique, an immunoenzymatic assay based on capture beads that are acquired through an assay kit, and the other steps of the process were performed with the aid of a flow cytometer with LegendPlex and IBM SPSS Statistics 22 software for data analysis. The results demonstrated that the clinical parameters of the molecular subtype of breast cancer, presence of estrogen receptors, presence of progesterone receptors, presence of HER2 receptors, menopause, and clinical staging did not influence the concentration of chemokines. It was possible to observe that chemokines have a positive correlation between them, and that there is an association between MIG concentration and the presence of p53 protein mutation. In the survival analyses, it was observed that the high concentration of the chemokine MIP-3alpha was associated with greater survival of patients in the initial stage, and that high concentrations of the chemokine MIP-1alpha were present in the group of patients with grade 3 tumors who survived less. Furthermore, MIP-1alpha was associated with greater recurrence-free survival of patients with lymphovascular invasion, and patients with high concentrations of MIG had a longer recurrence-free survival. Furthermore, patients unresponsive to the estrogen receptor had a reduction in overall survival when they had high concentrations of MCP-1 and MIG, and the same happened in patients with triple negative subtype with high concentrations of MCP-1. Based on these findings, the serological dosages of MIP-1alpha, MCP-1, MIG and MIP-3alpha did not present any difference between the studied groups. However, MIP-3alpha, MIP-1alpha and MIG are associated with survival and recurrence-free survival in the group of patients studied.